Analysis of Innovative Business Models in the Framework of Online Live Streaming: A Case Study Based on "EastBuy" - Ding, Boxin (Transactions on Economics, Business and Management Research, 2024)
The study of the "EastBuy" live streaming model focuses on its innovations and the root causes of its lasting appeal and influence. The study concludes that the rapid development and popularity of the "EastBuy" live broadcast is not accidental, but the result of a combination of strategies, such as talent building, user-centeredness, and the establishment of emotional connections. The core of the "EastBuy" live carry mode lies in the strong correlation established between the brand and the user, between the anchor and the user. This relevance in the emotional realization of the two-way anchor between the user and the brand, so that the audience's attention and trust in the live broadcast greatly increased. EastBuy has formed a unique new model by combining knowledge dissemination with live broadcasting. By constantly optimizing the talent team, improving the professionalism of the anchor, deepening the emotional connection with users, and innovating the live content. This model not only meets the audience's viewing needs, but also promotes the development of the live streaming industry.